(untitled) (International journal of artificial intelligence, 2025)
This study looks at euphemistic naming in Uzbek and English from both a narrow linguistic and a broad linguocultural viewpoint. Euphemization is a referential and evaluative linguistic technique used to lessen social taboos, negative connotations, or emotional distress. Having analyzed the works of Sheygal (2000), Reformatsky (1967), Shmelev (1977), and Burov (1994), the study separates two analytical dimensions: the textocentric, which sees euphemisms as practical instruments of cultural adaptation and communicative politeness, and the lexicocentric, which views euphemisms as closed lexical fields that substitute forbidden expressions. The study emphasizes how euphemistic designation reflects both subjective and objective elements, acting as a style identifier, a linguistic shield, and a means of expressing the speaker's identity. The theoretical framework is based on functional linguistics and enhanced by studies on terminology, modality, and communicative pragmatics. By integrating English and Uzbek findings, the paper demonstrates that euphemistic naming is a culturally mediated yet universally motivated process of secondary nomination that ensures ethical, aesthetic, and psychological harmony in communication.